Tadeusz Joteyko - a Musician, Conductor and Pedagogue - Katarzyna Rogozińska (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Tadeusz Joteyko is a Polish composer, conductor and pedagogue. From his work we can assume that he is a great patriot. He puts great emphasis on nationality in his works and connects it with historical events. Taking closer look on his pedagogic work, we can state a thesis that for this author the most important is common music education. His main goal was teaching youth music through music perception. But Tadeusz Joteyko is also an organiser and popularizer of musical life, a great promoter of stymulating role of culture in Polish society. One should also state that the literature on the subject is very limited. Information comes mainly fromthe 20th century, quite a lot of them come from musical or pedagogical magazines from that period.